2019
DOI: 10.1101/867747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogeography of equine infectious anemia virus

Abstract: ABSTRACTEquine Infectious Anemia virus (EIAV) is the causative agent of one of the most impacting infectious diseases affecting equids. EIAV is genetically diverse with several lineages circulating globally. To elucidate EIAV global spread patterns, we studied its spatiotemporal dynamics applying Bayesian phylodynamic analyses, using a worldwide compiled dataset composed of unique sequences of the gag gene. In addition, we performed a scoping review o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…High similarities were found among EIAV isolates from Bahia and Pantanal (present study) with European and North American strains [44]. A phylogeography to investigate the spatiotemporal dynamics of EIAV revealed Hungary as the origin of EIAV and described a migration route from Europe to the USA, then diversified and spread throughout Brazil [45]. We can observe a diversification or different origin of Brazilian strains by comparing Bahia and Pantanal gag sequences: Bahia's sequences are closer to the USA sequence, as described in the origin article [44], and BRA1/BRA2 are clustered with Italy/Ireland sequences (Supplementary Figure S8).…”
Section: Discussionsupporting
confidence: 57%
“…High similarities were found among EIAV isolates from Bahia and Pantanal (present study) with European and North American strains [44]. A phylogeography to investigate the spatiotemporal dynamics of EIAV revealed Hungary as the origin of EIAV and described a migration route from Europe to the USA, then diversified and spread throughout Brazil [45]. We can observe a diversification or different origin of Brazilian strains by comparing Bahia and Pantanal gag sequences: Bahia's sequences are closer to the USA sequence, as described in the origin article [44], and BRA1/BRA2 are clustered with Italy/Ireland sequences (Supplementary Figure S8).…”
Section: Discussionsupporting
confidence: 57%
“…Contrasting with the official stablished immunodiffusion test, ELISA is an immunoenzymatic technique that allows obtaining results in short periods of time, being more effective to issue criteria and authorization for the transfer of animals, adding efficiency to equine production and activities. Furthermore, recent studies have shown that the scientific production dedicated to the investigation of this virus in Mexico is deficient, despite being one of the main producing countries of equines [18]. The implementation of the diagnosis using ELISA systems in Mexico could be an alternative to expand EIA screening studies, as well as carry out epidemiologic and prevalence analyzes in higher risk areas because it is an economical technique with high capacity for processing a large number of samples in a single round test.…”
Section: Discussionmentioning
confidence: 99%
“…Equine are valuable for agriculture, sport, and meat production [16,17] and for all these activities is important count with a certainly diagnostic system that establish that animals are free of EIAV. Information of the virus in Mexico is limited [18]. The commercially available cELISA (IDEXX) designed to detect antibodies to p26 that has been approved for EIA diagnosis in several countries.…”
Section: Introductionmentioning
confidence: 99%